(untitled) (The Review of Diabetic Studies, 2025)
Background: Severe traumatic hemorrhage is a major cause of preventable mortality in the prehospital setting, where delays in resuscitation can rapidly lead to hemodynamic collapse and early coagulopathy. Prehospital blood transfusion (PBT) has emerged as a potential life-saving intervention aimed at stabilizing patients before arrival at definitive care. This systematic review examines the impact of PBT on mortality and key clinical outcomes among trauma patients with suspected or confirmed severe hemorrhage. Methods: A systematic search of PubMed, Embase, Web of Science, Scopus, and CENTRAL was conducted following PRISMA 2020 guidelines. Eligible studies included randomized trials, quasi-experimental studies, and observational cohort and case–control studies comparing PBT with standard prehospital care. Data extraction was performed independently by two reviewers, and risk of bias was assessed using Joanna Briggs Institute (JBI) tools. Outcomes included prehospital, 24-hour, in-hospital, and 30-day mortality, as well as physiological and transfusion-related secondary outcomes. Results: Eight studies met the inclusion criteria, representing military and civilian EMS systems, including ground EMS and HEMS services. Across most studies, PBT was associated with reduced early mortality—particularly within the first 24 hours—and improved hemodynamic stability on arrival, including higher systolic blood pressure and improved metabolic markers. Evidence regarding in-hospital and 30-day mortality was mixed, with some studies demonstrating benefit and others showing no significant difference. PBT was also associated with reduced crystalloid use, decreased activation of massive transfusion protocols, and a low incidence of transfusion-related complications. Conclusion: Prehospital blood transfusion appears to be a safe and effective intervention that can improve early survival and physiological outcomes among severely hemorrhaging trauma patients. While long-term mortality benefits remain inconsistent, the evidence supports expanding PBT programs—particularly in systems with prolonged transport times or high trauma burden. Further randomized trials and standardized reporting are required to determine optimal transfusion strategies and strengthen the evidence for widespread implementation.